Analisis Pertumbuhan Ekonomi Jawa Tengah Periode 2013 - 2017 - Primalasari, Anggi; Indarti, Iin; Adnanti, Wenny Ana (Jurnal Ilmiah Aset, 2019)
This study aims to determine and analyze the factors that influence economic growth in Central Java in the period 2013 to 2017. The aspects analyzed include variables economics growth (PDRB), Investment, Goverment Expendicture, Saving and Labor . The population of this study was 35 Regencies/Cities and the samples were 26 Regencies/Cities. The data used in this study were 130 data. The analysis technique used was multiple linier regressions. The result of this study indicated that Investment, Saving, and Labor had a positive effect on Economic Growth in Regencies/Cities of East Java in 2013-2017. But, that Goverment Expenditure had no effect on Economics Growth in Regencies/Cities of East Java in 2013-2017. While simultaneously indicated that Investment,Government Expenditure, Saving, and Labor had a significant effect on Economic Growthin Regencies/Cities of East Java in 2013-2017 with 38.9%, while remaining 61.1% wasinfluenced by other variables.